American foreign policy making and the democratic dilemmas - Spanier, John W.; Uslaner, Eric M. (Pacific Grove, Calif. : Brooks/Cole Pub. Co., 1989)
Focuses on the problems of making foreign policy in a democratic society.
Foreign policy in a democracy -- Presidential preeminence in the making of foreign policy -- The presidency and executive-legislative relations -- Congress: how silent a partner? -- The fourth circle I: public opinion, political parties, and the media -- The fourth circle II: local activists and interest groups -- The rational actor model and crisis decisions -- The bureaucratic politics model and noncrisis decisions -- Balancing the scales?
Includes bibliographical references (pages 379-384) and index.
Keywords: International relations -- Administration; United States -- Foreign relations administration